EVALUASI KINERJA SIMPANG EMPAT TAK BERSINYAL PADA JALAN RAYA TANJUNG – JALAN KARANGANYAR KABUPATEN PROBOLINGGO - Najibullah; Kurniawan, Achendri M.; Subkhan, Muhamad Fajar (Prokons: Jurnal Teknik Sipil, 2024)
Congestion is quite heavy at the unsignalized Jalan Raya Tanjung–Jalan Karanganyar intersection in Probolinggo Regency. Several stores and land transit connections linking Java and Bali can be found in this industrial region. Significant congestion is caused by high traffic densities. Examining the intersection’s performance under current and repaired conditions and comparing the operating costs of vehicles before and after treatment are the primary goals of this study. Number of vehicles, geometric circumstances, side obstructions, and traffic volumes are all examples of primary data used in this study. Intervening data sources include things like location maps, demographics, road functions, and vehicle operating cost components. The data was processed according to the MKJI approach as it was in 1997. With a service level of C and a congestion cost of Rp. 736,120, the analysis shows that the delay reached 16 seconds/smp before the repair. The alternative improvements resulted in a 12 seconds/smp delay with a service level of B and a congestion cost of Rp. 481,849 after the construction of a two-phase APILL, enlarging the approach lane, and regulating turning flow.